Expression of Newcastle disease virus genes and inflammatory biomarkers in Newcastle disease infected chicks - Abbas Kamil Shlaga; Hakeem Jawad Kadhim (University of Thi-Qar Journal of agricultural research, 2024)
In poultry, the devastating effect of Newcastle disease (ND) has been addressed; however, the inflammatory response of infected birds has received less attention. Therefore, the study was designed to detect the ND virus and find changes in the gene expression of inflammatory biomarkers in birds infected naturally with ND using reverse transcription-PCR (RT-PCR). The expression of the matrix (M) gene of NDV and inflammatory biomarkers like creative reactive protein (CRP), interleukin 6, interleukin-1 beta (IL-6, IL-1β), and gamma interferon (IFN-γ) genes was analyzed. Despite the fact that flocks were vaccinated against NDV using the LaSota vaccine, various clinical signs were observed in many flocks, and 60 suspected and 30 control samples were collected from 3 to 5 weeks old. Blood, liver, and tracheal swaps were sampled from suspected and control birds. However, the infected birds showed respiratory, digestive, and nervous signs. Further, typical postmortem symptoms such as mottled spleen, periventricular gland-tip hemorrhages, and cecal hemorrhages were seen. The NDV infection was initially confirmed using the NDV rapid test, which showed positive results in 52 out of 60 suspected samples (86.66%). To confirm the infection with NDV, RT-PCR was utilized to examine the expression of the M gene in the samples and revealed that only 27 (51.92%) out of 52 samples were positive. Thereafter, the mean antibody levels of ND-infected birds were significantly lower than those of uninfected birds. In contrast, inflammatory biomarkers’ gene expression exhibited an increase in their mRNA levels, indicating that the birds were infected with a viral infection and that there is inflammation in the body. To sum up, data suggest that the M gene could be used as a marker for identifying NDV in infected birds. Similarly, the NDV infection leads to a decrease in AB titers, which is associated with an increase in the gene expression of inflammatory biomarkers in infected birds. Therefore, serological tests as well as the molecular approach should always be considered in epidemic regions